(untitled) (World Bulletin of Management and Law, 2025)
In the era since the 20th century, undoubtedly, the widespread international terrorism crimes have caused tremendous social harm to human society. The international community, by responding with legislation, has been taking strict actions to punish international terrorism criminals and to fully restrain the breeding and spread of such phenomena. It must be acknowledged that up to now, the international community has been making proactive endeavors to rigorously punish international terrorism crimes and has attained significant achievements.